Effectiveness of a Comprehensive School-Based Oral Health Intervention Program on Periodontal Disease Outcomes: A Randomized Controlled Trial - Anuj Singh Parihar; M. S. Kalpana; Pooja Dwivedi; Meena Jain; Padmaja Swain; Fazil A. Nasyam (Journal of Pharmacy and Bioallied Sciences)
Background: Periodontitis is a prevalent oral health issue in rural India, contributing to tooth loss and systemic health complications. School-based oral health education programs offer a promising prevention and early intervention strategy. Objective: To assess the impact of a comprehensive school-based oral health program on periodontal disease prevalence and severity among school-aged children in rural Bhopal. Materials and Methods: A randomized controlled trial was conducted among 5000 children (10-15 years) in rural Bhopal. The intervention group received a 6-month program comprising oral hygiene instruction, dietary counseling, information on periodontitis, and facilitated dental checkups. The control group received no additional oral health education. Pre- and post-test assessments included clinical examinations (Community Periodontal Index, Gingival Index, Plaque Index) and oral health knowledge and practices questionnaire. Results: After six months, the intervention group showed significant reductions in periodontal indices (CPI: −0.45, P < 0.001; GI: −0.30, P < 0.001) and plaque levels (PI: −0.65, P < 0.001) compared to the control group. They also demonstrated significant improvements in oral health knowledge (P < 0.001) and reported oral hygiene practices (P < 0.001). Conclusion: A comprehensive school-based oral health education program is efficacious in improving periodontal health, knowledge, and practices among rural Indian children. The program’s success supports its potential for broader implementation as a sustainable and cost-effective public health intervention in similar settings.